2019
DOI: 10.1007/s13555-019-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Generalized Eruptive Keratoacanthoma of Grzybowski with Acitretin

Abstract: Introduction Keratoacanthomas (KA) are common cutaneous skin tumors originating from the hair follicles. Unlike squamous cell carcinoma, KA can regress spontaneously and have a benign evolution. Solitary KA is the most common form but familial multiple KA (Ferguson–Smith type), genetically predisposed KA (such as in xeroderma pigmentosum, or Muir–Torre syndrome), or sporadic multiple eruptive KA (Grzybowski type) have been described. Generalized eruptive KA of Grzybowski (GEKA) is a rare condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Widespread appearance of skin lesions on the body may also occur in connection with infectious agents such as HPV. The absence of viral material in a representative lesion in our patient is in line with findings of some authors [ 14 ], while others identified certain subtypes such as HPV39 in KA [ 10 ]. It should be mentioned that even sophisticated molecular laboratory tests may fail to detect HPV, as positivity is often lost in regressing warts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Widespread appearance of skin lesions on the body may also occur in connection with infectious agents such as HPV. The absence of viral material in a representative lesion in our patient is in line with findings of some authors [ 14 ], while others identified certain subtypes such as HPV39 in KA [ 10 ]. It should be mentioned that even sophisticated molecular laboratory tests may fail to detect HPV, as positivity is often lost in regressing warts.…”
Section: Discussionsupporting
confidence: 92%
“…GEKA is a rare condition with high disease burden, typically being more pruritic than singular lesions of KA. The papules, nodules, and tumors are widespread and may arise on all parts of the body, including mucosa [ 10 ]. The etiology of GEKA remains elusive; however, well-described risk factors include a variety of autoimmune diseases (e.g., rheumatoid arthritis, Sjögren’s syndrome), immunomodulating agents, and hematologic malignant diseases (e.g., multiple myeloma, myelodysplastic syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…GEKA is a rare variant of multiple keratoacanthomas, with only around 40 cases reported. 1 Its onset most commonly occurs between the fifth and seventh decades, without sex predilection. 2 Unlike other types of multiple keratoacanthomas, such as Ferguson-Smith or Witten and Zak, all cases are sporadic.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several factors have been proposed to play a role in its pathogenesis, including trauma, immunological abnormalities, ultraviolet radiation, chemical carcinogens, and viruses, particularly human papillomavirus. 1 , 3 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, retinoids were also widely used for the experiments of diverse human cancers due to their influences on the cell proliferation and apoptosis of multiple tumor cells . Currently, the commonly used retinoids were all‐trans‐retinoic acid (ATRA), acitretin, isotretinoin, and tazarotene . However, repeated and long‐term use of these drugs often caused a lot of adverse reactions like allergic reaction, dry skin, piercing, photosensitivity, and skin infection.…”
Section: Introductionmentioning
confidence: 99%